Effects of slot injection on detonation wavelet characteristics in a rotating detonation engine. (May 2021) - Yan, Chian; Teng, Honghui; Ng, Hoi Dick
Abstract: Two-dimensional numerical simulations are performed to investigate the effects of spatially discrete slot injection of reactants on the features of detonation wavelets in a rotating detonation engine (RDE). The detonation dynamics is described by a model based on the reactive Euler equations coupled with two-step, induction-reaction kinetics. By varying injection conditions and the chemical sensitivity of the reactive mixture, a parametric study is carried out to examine the influence of the injection-slot area ratio α on the detonation wavelet patterns and different flow features inside an RDE combustion chamber. The simulation results demonstrate that the injection conditions, i.e., stagnation temperature and pressure, have a similar influence on slot-ozzle rotating detonation wavelets (RDWs) as compared with the mini-nozzle RDWs reported in a previous study. The corresponding mass flow rate and inhomogeneity generated due to the presence of slot injection, however, play a key factor in the self-sustained rotating detonation and its frontal structure. Highlights: The detonation wavelets with slot injections are resolved computationally with GPU. Flow features are compared between the slot injection and micro-nozzle injection. The wavelet number dependence on slot injection stagnation properties are studied. The instabilities induced by the slot injections in rotating detonation are highlighted.